2022
DOI: 10.21203/rs.3.rs-1411694/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of rye inclusion in dog food on fecal microbiota and short-chain fatty acids

Abstract: BackgroundRye intake has been associated with beneficial effects on health in human interventions, possibly due to soluble dietary fiber in rye. In dogs, few studies have explored the effects on health of dietary fiber in general, and rye fiber in particular. The aim of this study was to investigate how inclusion of rye, compared with wheat, influenced fecal microbiota composition, short chain fatty acids (SCFA) and apparent total tract digestibility (ATTD) in dogs. Six male Beagle dogs (mean age 4.6 years, SE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
(42 reference statements)
1
3
1
Order By: Relevance
“…Statistical signi cance was likely not reached due to large inter-individual variation, and larger sample size would perhaps con rm a signi cant difference between diets. In agreement with ndings in the present study, our previous study showed signi cantly higher Prevotella abundance following the diet with highest inclusion of rye than following the wheat diet 21 . However, in that study whole-grain rye was compared to re ned wheat and the dietary inclusion level of rye was higher (50% of DM).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Statistical signi cance was likely not reached due to large inter-individual variation, and larger sample size would perhaps con rm a signi cant difference between diets. In agreement with ndings in the present study, our previous study showed signi cantly higher Prevotella abundance following the diet with highest inclusion of rye than following the wheat diet 21 . However, in that study whole-grain rye was compared to re ned wheat and the dietary inclusion level of rye was higher (50% of DM).…”
Section: Discussionsupporting
confidence: 93%
“…Catenibacterium is a common bacterial member of the gut microbiota in dogs, yet often of relatively low abundance 45,51,52 . In the present study it was one of the most abundant genera, with highest abundance in samples collected after diet R. In contrast, in our previous study this taxon decreased in abundance from a baseline level on adding rye to the diet 21 . The reason for the discrepancy is unknown.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations